Revenue determinants and tax export ability in the Malaysian tourism market - Mohebi, Mohammad (2012)
Based on the statistics, the number of Malaysian tourist arrivals grew by 25% during 2006-2008. Comparatively in the same period, the rate was 4% in Singapore and Thailand. A problem in the Malaysian tourism industry is that the growth rate of tourism revenue does not correspond to the growth rate of tourist arrivals. In comparison to Thailand and Singapore, Malaysia had more tourist arrivals but earned less income. Tourism expenditure is a source of private revenue. Private sector revenue depends on own price, income, substitution price, exchange rate and several other factors which are affecting the expenditure of tourists. In the public sector,tourism tax is a main source of government revenue from the tourism industry. Tax incidence and exportability depends on the price elasticity of supply and demand. This study is divided into two parts for analysis. Firstly, to examine the tax exportability, a system of supply and demand model is estimated using the W2SLS estimator. The data set includes quarterly time series from 1995q1 to 2009q4 (60 observations). In the second step, to determine the major factor which is affecting the expenditure of tourists, a panel gravity model has been used for 14 origin countries, from 1998 to 2009. In the simultaneous equation model most of the explanatory variables in demand equation are highly significant. The elasticity of income is less than unity and suggests that Malaysia is a cheap distance and it is not a luxury good. The demand is inelastic to the price but the supply is elastic in the short run. Hence, if the government imposes one Ringgit (Malaysian currency) tax on hotel room prices, the tourists pay is about 89 cents. Therefore, the Malaysian tourism market is tax exportable. The results of the expenditure model suggest that the Malaysian price index and distance have negative impact while per capita income of origin countries and Malaysian per capita income have positive impact on tourism expenditure. Our results also show that Singapore is a complementary destination meanwhile Thailand and Australia are substitute destinations for Malaysia. According to the 2020 vision, government and private sectors are required to finance tourism industry aims. Our suggestion for the Malaysian government is that they are able to export tax to tourists and obtain revenue in the short run. But in the long run, total tourist expenditure decreases considering our results on demand and supply elasticity. It should be noted that this occurs if we move on the demand curve, other factors that affect tourist’s flows being assumed constant. Based on the result of the simultaneous equations model, tourism equilibrium price has been calculated as well as the yearly trend for Malaysia. During the period of 1995 until 2000, the growth rate of the equilibrium price was greater than the consumer price index, which means that in the Malaysian tourism market, new infrastructure during this period had not been developed to keep pace with tourist arrivals. But after year 2002, exceeding demand was not able to explain the changes in tourism price.